1994
DOI: 10.1161/01.hyp.24.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of vascular angiotensin I-converting enzyme in hypertension.

Abstract: The angiotensin I-converting enzyme (ACE) gene is found on the locus that has been linked to high blood pressure after sodium loading in rats, so in the present study we investigated the role of vascular ACE for the pathophysi-ology of hypertension in the corresponding parental strains, Wistar-Kyoto (WKY) rats and stroke-prone spontaneously hypertensive rats (SHRSP), in basal conditions at different ages and after sodium loading. Blood pressure was already significantly enhanced in SHRSP from 4 weeks of age, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
5
14
0
Order By: Relevance
“…On the other hand, plasma ACE activity did not significantly differ among WKY rats, SHR-SP, and sodium-loaded SHR-SP. These results support previous findings (10,11). Therefore, blood pressure might have more influence in vascular than in plasma ACE-dependent angiotensin II formation (11).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, plasma ACE activity did not significantly differ among WKY rats, SHR-SP, and sodium-loaded SHR-SP. These results support previous findings (10,11). Therefore, blood pressure might have more influence in vascular than in plasma ACE-dependent angiotensin II formation (11).…”
Section: Discussionsupporting
confidence: 92%
“…We previously reported that ACE activity is significantly higher in the aortae of SHR-SP than WKY rats, and even more so in those of sodium-loaded SHR-SP than in SHR-SP (21). In genetically hypertensive models, such as SHR and SHR-SP, ACE expression in the vasculature is upregulated and angiotensin II action against blood vessels is strengthened (10,22). The present study found that telmisartan, but not valsartan, reduced ACE activity via its PPARγ agonistic effect, and this might result in a decrease of angiotensin II action including NAD(P)H oxidase in the vascular tissues.…”
Section: Fig 5 Ace Activities In Wky Rats Placebo (P)- Telmisartamentioning
confidence: 99%
“…By replacing drinking water with a 1% NaCl solution, these animals show accelerated organ damage such as stroke, cerebral edema, renal dysfunction, and cardiac hypertrophy (19,20). Sodium loading enhances the activity of angiotensin-converting enzyme (ACE) in the brain and aorta in these animals, which in turn, can exaggerate organ damage (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…By replacing drinking water with a 1% NaCl solution, organ damage such as stroke, cerebral edema, renal dysfunction, and cardiac hypertrophy are accelerated (Inada et al, 1995;Blezer et al, 1998). Sodium loading enhances the activity of ACE in the brain and aorta in these animals (Mizuno et al, 1981;Fernandes-Alfonso et al, 1994), which in turn can exaggerate organ damage (Bader, 2002;Hanes et al, 2004). Although many chronopharmacological profiles have been reported for antihypertensive agents, information concerning the dosing time-dependent prevention of organ damage is limited, and no information is available concerning the dosing time-dependent effect on survival rate.…”
Section: Discussionmentioning
confidence: 99%